Project Structuring and Financing in Kerala - Jency S (International Journal for Research in Engineering Application & Management (IJREAM), 2018)
Inadequate infrastructure is considered to be the biggest stumbling block in any country's growth. The economic plans and strategies would reach a dead end on this point alone. The general disillusionment with the public sector's performance, its inefficient and insensitive approach to consumer needs and government's poor fiscal position has triggered the breaking up of the government monopoly over infrastructure. While, there are several dimensions to the issue of private participation in infrastructure projects, the financing of such projects requires special attention. This study makes an attempt to have an overview of Financing Infrastructure through Project Financing and to examine the constrains in terms of finding adequate resources for financing infrastructure projects.